DENOMINASI MAYORITAS MUSLIM TERHADAP MINORITAS MUSLIM DI INDONESIA: STUDI FATWA MUI TENTANG ALIRAN KEBERAGAMAAN - Wicaksono, Syafril; Al-Asy Ari, Khoirul Hadi; El Adibah, Elisa Dourotun Nafis; Iffahasanah, Iffahasanah (Jurnal Ilmu Syariah dan Hukum (JISYAKU), 2024)
This research is a library research study on the results of fatwas produced by the MUI, the Indonesian Ulama Council, with the dimensions of several fatwas that are "indicated" of carrying out denominations of heterogeneity and pluralism of Islamic diversity in Indonesia, the theme raised is "Muslim Majority Denomination against Muslim Minorities in Indonesia: MUI Fatwa Study on Islamic Religious Flows in Indonesia" there are two important questions in this study, first how is the concept of Denomination in Islamic studies (genealogy, history and transformation)? and secondly, is there a Muslim Majority Denomination against Muslim Minorities in Indonesia: MUI Fatwa studies on religious sects in Indonesia? with historical studies and concept analysis in the form of content analysis to provide a very in-depth explanation of the concept of denomination in Islamic studies (starting from the study of denomination genealogy, historical studies related to the theory of religious denominations, and thirdly the matter of transformation of religious denominations) and secondly reading all fatwas about flow. The diversity issued by the MUI in Indonesia with the theory of the religious denomination, and what impact it has on the process of diversity in Indonesia. The results of this study indicate that religious denominations do occur in all corners of the world, this theory originates from religious denominations in Europe and it turns out that the pattern of denominations is almost the same in all other parts of the world, although several different cases are exceptions, and secondly, there are several indications related to MUI studies and fatwas related to religious sects have "strong indications" of a structured denomination pattern wrapped in study knowledge that is considered "representative" by the MUI itself and this dimension provides space for the existence of a Muslim Majority Denomination against Muslim Minorities in Indonesia